A Analisis Kesalahan Berbahasa Pada Artikel Jurnal Pragmatik Mahasiswa Pendidikan Pendidikan Bahasa dan Sastra Indonesia: Analisis Kesalahan Berbahasa Pada Artikel Jurnal Pragmatik Mahasiswa Pendidikan Pendidikan Bahasa dan Sastra Indonesia - magda, ivana (Universitas Negeri Surabaya, 2024)
The aim of this research is to find out language errors in articles written by one of the IndonesianLanguage and Literature education students. This research uses a qualitative descriptive researchmethod and applies the content analysis method. The main source of data is the words contained in the article, which indicate language errors. The data collection process is carried out by reading thearticles that are the object of analysis, and then noting the parts that contain language errors. Theresults of this research found language errors; three errors in writing capital letters, three errors inwriting italics, two errors in using punctuation marks, eight errors in writing words, and one error inwriting non-standard words. Keywords: Indonesian language, language errors, word, writing errors